Oleanolic acid modulates neuronal regeneration through KLF5-mediated FGF13 mRNA degradation to alleviate Alzheimer’s disease-like cognitive dysfunction - Dan Ren; Jiangxi Xu; Lan Xiao; Ting Zhang; Biyan Li; Ruomeng Li; Hong Zhu (Journal of Molecular Medicine, 2026)

Bushen Huoxue Acupuncture alleviates alzheimer’s disease progression via the E3 ubiquitin ligase SMURF2‑mediated ubiquitination of LAPTM5 - Ruomeng Li; Ting Zhang; Dan Ren; Hong Zhu; Jiangxi Xu; Lan Xiao (Metabolic Brain Disease, 2026)

Iron plaque-mediated control of GenX accumulation by size-dependent α-Fe2O3 nanoparticles in hydroponic lettuce - Yaxin Guo; Ruomeng Li; Huijie Hu; Cuiping Wang; Hongwen Sun (Journal of Environmental Management, 2026)

Ecotoxicological responses to 6PPD-Q: Oxidative stress, gene expression dysregulation, and transcriptomic alterations in Eisenia fetida - Xiaoyi Wang; Qian Wang; Huijuan Lv; Xiangfeng Yao; Xianxu Li; Ruomeng Shi; Jia Ding; Ravil Baibekov; Lubsan-zondy Budazhapov; Jun Wang (Applied Soil Ecology, 2026)

Ecotoxicological effects of fluensulfone on non-target soil organisms: Phenotypic and molecular toxicity responses in Eisenia fetida - Qian Wang; Xiangfeng Yao; Ruomeng Shi; Yali Zhou; Huijuan Lv; Xianxu Li; Zhuran Hu; Lubsan-zondy Budazhapov; Jun Wang (Journal of Environmental Management, 2026)

Effect of biochar-derived dissolved organic matter on antibiotics migration in soil: Soil carbon, aggregates, and microorganism community structures - Ruomeng Li; Yaxin Guo; Yanan Xue; Xuejiao Tang; Cuiping Wang (Journal of Environmental Chemical Engineering, 2025)

Antagonistic toxicity of co-exposure to DEHP and sulfadiazine in Eisenia fetida: Multi-level responses and molecular insights - Ruomeng Shi; Xianxu Li; Huijuan Lv; Qian Wang; Xiangfeng Yao; Yeji Zhang; Huiyan Yang; Jia Ding; Lubsan-zondy Budazhapov; Jun Wang (Journal of Hazardous Materials, 2025)

Insight into how fermentation might contribute to the distinctiveness of Australian coffee - Ruomeng Li; Cristian Varela; Damian Espinase Nandorfy; Anthony R. Borneman; Laura J. Hale; David W. Jeffery (Food Chemistry, 2025)

Bushen Huoxue acupuncture ameliorates Alzheimer’s disease by upregulating MARCHF3 to induce NLRP3 ubiquitination and inhibit caspase-1-dependent pyroptosis - Hong Zhu; Ting Zhang; Ruomeng Li; Dan Ren; Jiangxi Xu; Lan Xiao (Metabolic Brain Disease, 2024)

Quantitative Proteomic and Phosphoproteomic Analyses Reveal a Role of Death-Associated Protein Kinase 1 in Regulating Hippocampal Synapse - Yuan Tian; Xiaoqing Zheng; Ruomeng Li; Li Hu; Xindong Shui; Long Wang; Dongmei Chen; Tae Ho Lee; Tao Zhang (Molecular Neurobiology, 2024)

Study on Gas Transport Performance in Perforated Gas Diffusion Layer by Lattice Boltzmann Method - Ziheng Jiang; Guogang Yang; Qiuwan Shen; Shian Li; Jiadong Liao; Hao Wang; Zhonghua Sheng; Ruomeng Ying; Zheng Li; Guoling Zhang; Hongpeng Zhang (Transport in Porous Media, 2022)

Variation and evolution of C:N ratio among different organs enable plants to adapt to N‐limited environments - Jiahui Zhang; Nianpeng He; Congcong Liu; Li Xu; Zhi Chen; Ying Li; Ruomeng Wang; Guirui Yu; Wei Sun; Chunwang Xiao; Han Y. H. Chen; Peter B. Reich (Global Change Biology, 2020)
Carbon (C) and nitrogen (N) are the primary elements involved in the growth and development of plants. The C:N ratio is an indicator of nitrogen use efficiency (NUE) and an input parameter for some ecological and ecosystem models. However, knowledge remains limited about the convergent or divergent variation in the C:N ratios among different plant organs (e.g., leaf, branch, trunk, and root) and how evolution and environment affect the coefficient shifts. Using systematic measurements of the leaf–branch–trunk–root of 2,139 species from tropical to cold‐temperate forests, we comprehensively evaluated variation in C:N ratio in different organs in different taxa and forest types. The ratios showed convergence in the direction of change but divergence in the rate of change. Plants evolved toward lower C:N ratios in the leaf and branch, with N playing a more important role than C. The C:N ratio of plant organs (except for the leaf) was constrained by phylogeny, but not strongly. Both the change of C:N during evolution and its spatial variation (lower C:N ratio at midlatitudes) help develop the adaptive growth hypothesis. That is, plants with a higher C:N ratio promote NUE under strong N‐limited conditions to ensure survival priority, whereas plants with a lower C:N ratio under less N‐limited environments benefit growth priority. In nature, larger proportion of species with a high C:N ratio enabled communities to inhabit more N‐limited conditions. Our results provide new insights on the evolution and drivers of C:N ratio among different plant organs, as well as provide a quantitative basis to optimize land surface process models.

Combining the Fisher Feature Extraction and Support Vector Machine Methods to Identify the Water Inrush Source: A Case Study of the Wuhai Mining Area - Donglin Dong; Zhiyuan Chen; Gang Lin; Xiang Li; Ruomeng Zhang; Yuan Ji (Mine Water and the Environment, 2019)